Comparative Study endowment Productive in Southern Thailand and in Indonesia - Syahputri, Dela; Rangkuti, Ahmad Zuhri (Institute Of computer Science (IOCS), 2025)
This study compares the implementation of productive waqf in two Islamic educational institutions: Chariyasasana Islam School in Songkhla, Thailand, and Al-Uswah Kuala Islamic Boarding School in Langkat, Indonesia. Using a qualitative method through interviews, observation, and documentation, the study explores waqf management models, resources, challenges, and socio-economic impacts. Chariyasasana integrates waqf with zakat, infaq, and sedekah, which together fund about 45% of its operational needs. These funds support income-generating activities such as fish farming, which help finance scholarships and school programs. Al-Uswah focuses on developing a school cooperative and small businesses like a bakery and minimarket, contributing around 30% of the school’s income and helping subsidize tuition for underprivileged students. Both institutions face challenges such as limited regulatory frameworks, shortage of skilled human resources, and low public awareness of productive waqf. Despite this, both show positive outcomes: improved financial self-reliance, broader student access, and stronger community engagement. These findings highlight the potential of productive waqf to sustain Islamic education and support local economies. The study recommends enhancing cross-border cooperation, developing clear regulations, and providing training for waqf managers to replicate and scale successful models in other regions